Checklist of beetles (Coleoptera) from the cork oak forest of Larache (Morocco). - Amine Samih; Noureddin Maatouf; Sergi Trócoli; Hamza Habbaz; Latifa Rohi (نامه انجمن حشره‌شناسی ایران)
Abstract The cork oak forest of Larache, a vital part of Morocco Atlantic coastal cork oak woodlands, plays a crucial role in supporting local ecosystems and human societies. However, it is increasingly threatened by intensive agriculture and other anthropogenic pressures, resulting in habitat loss for insects, including beetle communities. This study aimed to establish a comprehensive inventory of beetles in the cork oak forest of Larache over two consecutive years (2021 and 2022) by examining beetles associated with different vegetative landscapes using various trapping techniques (pitfall and pan traps) and direct surveys. The results revealed 180 species from 37 families, including 9 endemic species, 33 species newly recorded in Morocco, 13 saproxylic species and 10 species listed on the Red List (7 saproxylic and 3 coprophagous species). This diversity underscores the ecological importance of the cork oak forest of Larache and highlights the urgent need for conservation measures and the promotion of suitable habitats to protect these insect communities.